Development, Reliability, and Validity of the Influences of Digital Technologies on Human Behavior in Public Space Scale Tested by Spatial Design Experts - Altanlar, Asli; Aktan, Esin Ozlem Aktuglu; Eren, Ibrahim (SAGE PUBLICATIONS INC, 2024)
The widespread use of digital technologies and online social networks causes a shift that has a pronounced impact on public space, public life, and public space design. However, research into this transformation is quite constrained. This study aims to illuminate how digital technologies influence individuals and their behavior in public spaces. A comprehensive conceptual scale was developed in the study to assess the impact of digital technology use on human behavior in public spaces. A structural equation model (SEM) was proposed after testing the scale's construct validity. According to the findings, the factors influencing the scale were social isolation (F1), media influence (F2), placelessness and/or homogeneity (F3), techno-stress-related social anxiety (F4), and digital addiction (F5). The SEM (Structural Equation Modeling) results demonstrated strong relationships among these factors, with digital addiction significantly predicting social isolation (beta = .90; p < .01) and placelessness (beta = .74; p < .01). The media influence factor had the most substantial effect on techno-stress-related social anxiety. This study contributes significantly to the literature by understanding the influences of digital technologies on public life and adapting public space design to this new reality. The findings also guide prospective studies into the effects of digital technologies in public spaces, offering valuable insights for urban planning, social psychology, architecture, and social sciences research.
Keywords: public life; online social networks; human behavior; social isolation; technological anxiety; digitization and urban life; COLLEGE-STUDENTS; FACEBOOK USE; DEPRESSION; USAGE; Social Sciences - Other Topics